Development of the Constructive Alignment Evaluation Instrument for Lecturers of Teachers Education Institutes - Daud Md Jani, Md; Abdul Latif, Adibah; Talib, Rohaya (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to build the constructs and sub-constructs for the Constructive Alignment Evaluation Instrument (CAEI) for lecturers of Teachers Education Institutes (TEIs) based on the experts' views. Interviews involving a total of five experts from TEIs in Malaysia were conducted using purposive sampling. The experts involved were the chairman of the TEI Assessment Committee, the internal examiner expert, the chairman of the MQA Committee, the chairman of the ISO Secretariat, and the assessment coordinator of the department. The interview data was analyzed thematically using NVivo software. Based on the interview, it was found that there were certain shortcomings to be addressed in the implementation of constructive alignment among TEIs’ lecturers. The constructs driven from the interview were knowledge and practice, comprising a total of six sub-constructs, namely, learning outcomes, teaching and learning activities, assessment of assignment, evaluation and grading, learning context, and students learning time. The sub-construct of learning outcomes consists of four elements: Program Educational Objectives, Program Learning Outcomes, Teaching Taxonomy, and Course Learning Outcomes. The sub-construct of teaching and learning activities is also divided into four elements: teaching and learning planning, mapping of knowledge type, interactive teaching, and class management. Meanwhile, the subconstruct of assessment assignment contains elements such as formative and summative, authenticating, converging and diverging assessments, and Bloom's Taxonomy. As for students learning time, its sub-construct includes elements of implementation of learning hours, credit, and learning load. The sub-construct of evaluation and grading contains elements of validity and reliability, criterion references, norm references, and evaluation based on learning outcomes. Finally, the sub-construct of learning context is divided into five elements: metacognitive control, reflective learning, teaching quality and student activity, formative feedback, and motivational approach. Based on the results obtained, the constructive alignment evaluation instrument should include all the constructs and sub-constructs identified.